Pollution Level, Sources, and Lung Cancer Risk of PM10-Bound Polycyclic Aromatic Hydrocarbons (PAHs) in Summer in Nanjing, China - Shiqi Sun; Zhonghuan Xia; Tao Wang; Minmin Wu; Qianqian Zhang; Jing Yin; Yanchi Zhou; Hao Yang; Wenqi Wang; Yueming Yu; Jing Xu; Cheng Chen (Journal of Chemistry)
This study concentrated on the pollution level, sources, and lung cancer risk of PM10-bound polycyclic aromatic hydrocarbons (PAHs) in summer in Nanjing, China. PM10 samples were collected in summer of the year 2015 in Nanjing. 16 USEPA (United States Environmental Protection Agency) priority PAHs were extracted and analyzed after sampling. The mean concentrations of PAHs and BaPeq were 7.49±2.60 and 1.21±0.24 ng/m3, respectively, being in a middle level among results from regions worldwide. According to the results of diagnostic ratios, PAHs originated mainly from traffic exhaust, especially diesel vehicle emissions. Owing to the inhalation exposure, the median values of incremental lung cancer risk (ILCR) were estimated to be 3.36×10-8, 2.50×10-8, 1.69×10-7, 2.54×10-8, 1.38×10-7, 1.18×10-7, 1.27×10-7, and 1.11×10-7 for boys, male adolescents, male adults, male seniors, girls, female adolescents, female adults, and female seniors, respectively, indicating low potential lung cancer risk.